University - executive: Towards a coordination relation - Ruiz Guzmán, Alfredo (Revista Universidad de Guayaquil, 2010)
The debate on the new Superior Education Organic Law project, including the management organ- isms arising from it, demands an understanding of the public University reality, which has been seriously affected by both a social crisis derived from the neoliberal period and the dilapidation of the Social State of Law. Furthermore, it also demands a deeper meditation on the comprehensive meaning of the new constitutionalist paradigm bound by the current Constitution, which conditions the legal build-up lawfulness in strict relation to its contents. It must be kept in mind that the current Constitution settles terms for the upcoming Law to establish coordination mechanisms between The Executive Power and the Superior Education System in order to legally design the new conception of such law together with a national development standard. In the event that such Law project may include a subordinated relation in favor of The Executive Power, it would go against the Constitution, since it would not only deny the responsible autonomy and the co-government principles, but also the possibility of a coordinated relationship as an unique requirement to achieve the new model of our Superior Education. Consequently such Law must include the organisms of the superior education system, considering the principles above mentioned plus the ones linked to the Executive Power but independently, so that the coordinated relationship may be established among them as established by the Constitution.